REFLECTIVE PEDAGOGY AS A THEORETICAL FRAMEWORK IN FOREIGN LANGUAGE EDUCATION - Bakhriddinova Dildora Dilshodovna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Reflective pedagogy has gained increasing attention in foreign language education as a learner-centered and teacher-development-oriented theoretical framework. It emphasizes conscious reflection on teaching practices, learning processes, and classroom interaction in order to improve instructional effectiveness and learner autonomy. This article explores reflective pedagogy as a theoretical foundation in foreign language education, examining its principles, pedagogical value, and relevance in contemporary educational contexts. Particular attention is given to its role in fostering critical thinking, professional growth, and meaningful language learning. The study highlights how reflective pedagogy contributes to adaptive teaching practices and sustainable educational development in language classrooms.